2018
DOI: 10.3379/msjmag.1803r009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hysteresis Measurement of Magnetic Nanoparticles with Aligned Easy Axes

Abstract: Magnetic particle imaging (MPI) is a novel diagnostic imaging technique based on the use of magnetic nanoparticles (MNPs). Investigating the magnetic properties of magnetic nanoparticles is important for achieving a high spatial and temporal resolution in MPI. In this study, -Fe2O3 nanoparticles (core diameter: dc = 4 nm), Fe3O4 nanoparticles (dc = 20-30 nm), and Resovist ® were immobilized in a DC magnetic field with their easy axes aligned. DC and AC magnetization curves were measured for the prepared MNPs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The increasing tendencies of the coercive field in the easy axis and hard axis samples are similar to those in the magnetic field intensity of 4 kA/m. We observed the change in the orientation of the magnetization by the numerically simulation with regard to the MNP in core diameter of 5±2 nm (mean±SD), when the field intensity was changed from -16 kA/m to 16 kA/m at the field frequency of 100 kHz 11) . Our numerical simulation revealed that the magnetization is oriented to the opposite direction of the applied field without reversal in the easy axis sample because of the anisotropy toward the easy axis.…”
Section: Ac Magnetization Curvesmentioning
confidence: 91%
See 2 more Smart Citations
“…The increasing tendencies of the coercive field in the easy axis and hard axis samples are similar to those in the magnetic field intensity of 4 kA/m. We observed the change in the orientation of the magnetization by the numerically simulation with regard to the MNP in core diameter of 5±2 nm (mean±SD), when the field intensity was changed from -16 kA/m to 16 kA/m at the field frequency of 100 kHz 11) . Our numerical simulation revealed that the magnetization is oriented to the opposite direction of the applied field without reversal in the easy axis sample because of the anisotropy toward the easy axis.…”
Section: Ac Magnetization Curvesmentioning
confidence: 91%
“…Figure 1 (a-d) shows the samples for experiment. The intensity of the DC field during the preparation of the samples with aligned easy axes was 575 kA/m 11) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the magnetocrystalline anisotropy was not observed during the dynamic magnetization process in this measurement under H AC = 4 kA/m. The anisotropic features in a dynamic magnetization process are observed when the magnetic field larger than the anisotropy energy is applied to the samples [ 11 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…1(c). With decreasing θ, the magnetization distribution was strongly aligned along the direction of the applied field, owing to the reduced anisotropy energy barrier 9),32), 33) . Two nodes connected by a line show the continuous trajectory of the magnetization in Fig.…”
Section: Time Evolution Of Magnetization and Easy Axis Orientationsmentioning
confidence: 99%